1987
DOI: 10.1111/j.1432-1033.1987.tb10891.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between beta-adrenoceptor regulation and beta-adrenergic responsiveness in hepatocytes. Studies on acquisition, desensitization and resensitization of isoproterenol-sensitive adenylate cyclase in primary culture

Abstract: The role of β‐adrenoceptor regulation in the mechnisms controlling β‐adrenergic responsiveness in hepatocytes was explored, using primary monolayer cultures. When plated in vitro, these cells gradually acquire a strong catecholamine‐sensitive adenylate cyclase activity and an enhanced ability to bind the β‐adrenoceptor ligand [125I]iodocyanopindolol (125ICYP). Examination of the time course showed that the increase in the number of 125ICYP binding sites was detectable within 1–2 h of culturing and slightly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
4
13
2
Order By: Relevance
“…Itoh et al [47] reported that treatment of membranes from hepatocytes with pertussis toxin increased the isoproterenol-sensitive adenylate cyclase activity. This is supported by our data, but, in contrast to the results of Itoh et al [47], we found as in other studies [45,49,501 that the glucagon responsiveness was also augmented, which argues against a selective effect of the toxin on /?-adrenoceptor-mediated functions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Itoh et al [47] reported that treatment of membranes from hepatocytes with pertussis toxin increased the isoproterenol-sensitive adenylate cyclase activity. This is supported by our data, but, in contrast to the results of Itoh et al [47], we found as in other studies [45,49,501 that the glucagon responsiveness was also augmented, which argues against a selective effect of the toxin on /?-adrenoceptor-mediated functions.…”
Section: Discussionsupporting
confidence: 84%
“…[42]) was amplified when the cells were pretreated with pertussis toxin, as demonstrated by the augmented effect of epinephrine and isoproterenol (Table 1). These results, and other recent data [45,461, also indicate that hepatocytes cultured in vitro as primary monolayers retain the capacity to react to pertussis toxin, and thus do not support the finding in another study [47] that the response of the liver cells to the toxin is lost during culturing. Pertussis toxin was also strongly effective when added to cultured hepatocytes as much as 5 days after plating (data not shown).…”
Section: Effect Of Pertussis Toxin On the C A M P Responses To Hormoncontrasting
confidence: 92%
See 1 more Smart Citation
“…maximum left ventricular pressure, heart rate and blood pressure were severely attenuated in the isoprenaline-treated desensitized rats. Moreover, other working groups demonstrated in cultured heart cells or cultured hepatocytes that downregulation of ␤ -adrenoceptors might occur within the range of hours and that ␤ -blocker treatment is able to overcome this downregulation [19,20] . Thus, it is in good accordance with the literature that in our cell culture model ␤ -adrenoceptors are downregulated after isoprenaline treatment and that S-or RS-metoprolol upregulate ␤ 1 -adrenoceptors, thereby restoring the ␤ 1 -adrenoceptor/G s /adenylyl cyclase pathway, whereas the R-enantiomer, due to its lack of activity on ␤ -adrenoceptors, is not able to upregulate ␤ 1 -adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p-adrenoceptors are linked to adenylyl cyclase activation, and bidirectional effects of cyclic AMP on hepatocyte DNA synthesis have been found (Brgnstad et al, 1983;Thoresen et al, 1990). One reason why it is particularly desirable to obtain more direct information about growth effects mediated through P-adrenoceptors is the fact that in various conditions associated with hepatocyte growth, such as the perinatal period (Christoffersen et al, 1973), regenerating liver (Brgnstad and Christoffersen, 1980;Aggerbeck et al, 1983;HuertaBahena et al, 1983;Sandnes et al, 19861, and upon culturing of hepatocytes (Nakamura et al, 1983;Refsnes et al, 1983Refsnes et al, , 1987Christoffersen et al, 19841, there is a dramatic elevation of the P-adrenergic responsiveness of the hepatic adenylyl cyclase, and a several-fold increase in the number of P-adrenoceptors. The functional consequence of these changes, as related to growth control, is not clear.…”
mentioning
confidence: 94%